Ovarian diseases in Holstein dairy cows, factors determining their occurrence and impact on reproduction traits and breeding costs - CITEK, J; NEMECKOVA, D; STADNIK, L; STUPKA, R (The Indian Journal of Animal Sciences, 2017)
The aim of this study was to assess the factors determining ovarian disorders occurrence and quantify the influence of ovarian diseases occurrence on fertility traits and breeding costs in selected herd of dairy cows. Holstein cows (67) calved between 1 January 2012 and 30 August 2012 were monitored. Since 80 days postpartum cows with BCS higher than 2.5 and increasing BCS tendency were included into the synchronization program. Higher parity and summer calving season caused higher ovarian disease occurrence. Only slight nonsignificant relationship between cystic ovarian disease and energy balance was observed. Cows with detected cystic ovarian disease (COD) had significantly longer days open period for 24 days, longer calving to first service interval for 17 days and higher number of services per conception for 0.2 than cows without COD. Owing to higher number of services per conception in cows with COD, the breeding costs increased significantly for 258 CZK (14.25 USD). Energy balance traits did not differ significantly in relationship with COD occurrence, only slight decrease in otherwise higher BCS was detected in the first month of lactation in cows with COD occurrence.